PEMBERDAYAAN PEKERJA MIGRAN DI SINGAPURA MELALUI DIGITALISASI PENGELOLAAN KEUANGAN DAN PENGEMBANGAN UMKM - Septiani, Nisa (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2025)
This Community Engagement Program aims to empower Indonesian migrant workers in Singapore by enhancing their financial literacy and digital-based business management skills. Despite their significant economic potential, many migrant workers face limitations in managing personal finances and preparing for economic sustainability after working abroad. This program provides practical training in financial record-keeping, budgeting, and the use of digital technology to support the development of Micro, Small, and Medium Enterprises (MSMEs). The methods employed include interactive workshops, case-based training, and hands-on assistance in using digital financial applications. The results indicate an increased understanding among participants regarding the importance of separating personal and business finances, as well as improved ability to prepare simple financial reports digitally. This initiative not only promotes economic self-reliance among migrant workers but also strengthens their contribution to national development through digital entrepreneurship. The program is expected to serve as a model for empowering the Indonesian diaspora through financial and technological literacy.